Syvällinen tapaustutkimusopas - Kröger, Markus (Terra, 2008)
Tapaustutkimuksen taito / Markus Laine, Jarkko Bamberg & Pekka Jokinen (toim.). Helsinki : Gaudeamus, 2007.
Keywords: Tapaustutkimuksen taito; sosiaalitutkimus - tutkimusmenetelmät; yhteiskuntatieteet - tutkimusmenetelmät